In-service analysis of tram wheel set life - Stanisław MŁYNARSKI; Paweł PIEC (Transport Problems, 2012)
The paper presents some results of in-service tests on tram wheel set life. The measurements of wheel rim undercut and wear on the rolling diameter of tram wheel set wheels are a data base for calculating tram rolling wheel life in two aspects: wheel operation conditions and materials from which the wheels were made.